2002
DOI: 10.2136/sssaj2002.4400
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Water Retention Curves for Wettable and Water‐Repellent Soils

Abstract: The capillary pressure (ψ) in unsaturated porous media is known to be a function of temperature (T). Temperature affects the surface tension (σ) of the pore water, but possibly also the angle of contact (γ). Because information on the temperature dependence of γ in porous media is rare, we conducted experiments with three wettable soils and their hydrophobic counterparts. The objectives were (i) to determine the temperature dependence of the water retention curve (WRC) for wettable and water-repellent soils, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…Since it is related to the air-entry value, α -1 in the case of hydrophilic soil is bigger than hydrophobic soil. This observation coincides with the previously reported experimental results for volcanic ash soil (Kawamoto, Moldrup et al 2007, Karunarathna, Chhoden et al 2010) and other various soils (Bachmann, Horton et al 2002).…”
Section: Fig 3 Soil-water Characteristic Curves For Hydrophilic Andsupporting
confidence: 94%
“…Since it is related to the air-entry value, α -1 in the case of hydrophilic soil is bigger than hydrophobic soil. This observation coincides with the previously reported experimental results for volcanic ash soil (Kawamoto, Moldrup et al 2007, Karunarathna, Chhoden et al 2010) and other various soils (Bachmann, Horton et al 2002).…”
Section: Fig 3 Soil-water Characteristic Curves For Hydrophilic Andsupporting
confidence: 94%
“…Where is surface tension of water (MT 2 ),ˇis the contact angle taken as 40°for moderately hydrophobic organic soils (Bachmann et al, 2002;, is water density (ML 3 ), g is gravity acceleration (LT 2 ). In this study, it is assumed that the equivalent pores smaller than the r value estimated by Equation (3) are full of water and responsible for 100% of the water flux for a given pressure head.…”
Section: Tension Infiltrometer (Ti) and Water-conducting Porositymentioning
confidence: 99%
“…(2) is F. However, experiments by Bachmann et al (2002) found that F decreased by an amount in the range of 1 degree to 8.5 degrees when the temperature was increased from 5-C to 38-C. Again, this would make only a small contribution to the temperature dependence, dB/dT. We note that F has been found to decrease with increasing amounts of dissolved organic matter in solution (Arye et al, 2008;Chen and Schnitzer, 1978;Tschapek et al, 1976).…”
mentioning
confidence: 59%